Intervention and Measures Taken on Comprehensive Health of the People Living in Yazd Eskan Neighborhood - Parisa Shojaei; Salimeh Zare Abdollahi; Mohammad Hasan Lotfi; Hosein Malekafzali (Gonabad University of Medical Sciences, 2021)
Background: The community participation concept has different implications for various individuals. Methods: This research was Community-Based Participatory Research (CBPR), which was done in Yazd. The settlement area with a population of 16,000 people is located on the western outskirts of Yazd. With the implementation of health transformation programs in the 11th government, first, the health base in 2016 and then, Dr. Malekafzali Comprehensive Health Services Center in this area have been set up and started to work in 2016 to provide various health services to the residents of this area. Considering the potentials of this neighborhood, including high social cohesion and the existence of a dynamic and popular non-governmental organization, since 2017, this place has been a candidate for the implementation of empowerment and optimal development of neighborhood health (Tabassom project). The steps of implementing the optimal Health development plan (Tabasaom) involved five steps of the area identification, organizing, empowerment, requirement assessment, and intervention and action. The stage of intervention and action was covered in this article. Results: Most of the problems that appeared in this study were non-health issues, encompassing a wide range of issues in other social, cultural, and economic fields. Conclusion: Identified issues consisted of a wide variety of problems that were needed to be resolved through interdisciplinary activities, the support of managers and officials, and the active participation of the community.